Improving the quality of care pathways for sarcoma patients and the advantages of using WCISU’s (Welsh Cancer Intelligence Surveillance Unit) national cancer registry - Griffiths, Rowena; Akbari, Ashley; Huws, Dyfed; Lyons, Ronan; Rolles, Martin; Vass, Johanne (International Journal of Population Data Science, 2018)
Introduction Soft Tissue Sarcoma (STS) diagnosis is difficult due to its nature and the variability of its occurrence on the body. To improve patient outcomes a better understanding was needed of the care pathways experienced by the patient from initial presentation to final treatment. Objectives and Approach Several items of information are necessary, within the data, to identify a care pathway. A correct STS diagnosis, a presentation date or first investigation date, a diagnosis date and any subsequent treatment dates. Identifying cases in hospital data, using International Classification of Diseases (ICD10) codes - C40, C41, C47 and C49 - based on cancer site - can miss cases and cause difficulties when trying to distinguish the difference between the investigation and treatment stages. Having access to WCISU’s national cancer registry, proved advantageous and enabled the routine data to be validated. Results Attempts to identify differences between investigative and treatment procedures using the procedure codes available in hospital data was unhelpful due to variations in coding. However, WCISU’s national cancer registry records all cases of cancer diagnosed in Wales using both ICD10 and International Classification of Diseases for Oncology codes to record cancer morphology. In addition, it records the date of diagnosis and treatment start dates. Using the cancer registry it was possible to cross-check the cases extracted from the hospital data and identify the diagnosis and treatment dates. By matching the treatment dates back to the hospital data it then became possible to analyse the procedure codes to see how many treatments were being delivered, the type of treatment and the periods covered. Conclusion/Implications Once accurate diagnosis and treatments dates were identified, it was possible to drill further into the hospital data to see the finer detail of the procedures the patient received. Utilising independent data sources made it possible to develop an enriched view of patient care pathways from diagnosis through to treatment.